Interaction mechanism between refractory and melts in iron bath smelting reduction process - Qiu G.B.; Xu Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The corrosion behavior of three sorts of refractories based on alumina-graphite were studied by immersion tests. The melts included smelting reduction molten slag and corresponding carbon saturated molten iron. The influence of test temperature, FeO content in slag and specimen rotative velocity on the corrosion rate of refractories was examined. By means of SEM and EDS, the microstructure change of the refractories after immersion test in kinds of melts was studied. The morphology of the deteriorated layer showed the corrosion extent of refractories. With the addition of zirconia and titania into the refractories, the corrosion rate changed to some extent. The corrosion rate of three sorts of refractories increased dramatically with the increasing FeO content in smelting reduction slag. Compared with alumina-graphite refractory and alumina-graphite-zirconia refractory, alumina-graphite-titania refractory had stronger corrosion resistance in the smelting reduction conditions. By the results of SEM and EDS, the corrosion mechanism of refractories was developed.